Women in Civil Engineering: A Literature Review of Barriers, Stress, and Alignment with the Sustainable Development Goals - Syadza Nabila Yusna; Vivid Lucha Deanggi (G-Tech: Jurnal Teknologi Terapan, 2025)
Research across various countries has shown that women in civil engineering and construction still face barriers that limit their participation and career advancement. These include gender bias, unsafe or inflexible work environments, limited mentorship access, and difficulties balancing work and personal life. Such conditions harm women’s mental health, job satisfaction, and long-term retention in the industry. This study analyzes these challenges and proposes strategies to address them through a qualitative literature review of previous research conducted in several countries, including Indonesia. The review identifies recurring patterns of inequality and examines how these barriers relate to the Sustainable Development Goals (SDGs), particularly those concerning health and well-being, education, gender equality, and decent work. The findings demonstrate that coordinated, evidence-based efforts involving inclusive workplace policies, equitable leadership, mentorship, and institutional support are crucial for enhancing women’s participation, well-being, and career sustainability. This review highlights that promoting gender equality in civil engineering is not only a matter of social justice but also a key driver of innovation, sustainability, and industry resilience.